Competency and Sustainability Integration in Enhancing Maritime Vocational Training for Deck Officers : Systematic Literature Review and Qualitative Analysis of Perspectives - Riyanto Riyanto; Cris Kuntadi; Larsen Barasa; Irene Evi Krismawati; Yayu Nopriani Martha; Marudut Bernadtua Simanjuntak (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
The growing complexity of maritime operations demands deck officers with advanced competencies and a strong understanding of sustainability principles. This study addresses critical gaps in maritime vocational education by exploring the effectiveness of current training programs, the integration of sustainability, and the role of technology-driven approaches. While previous research has focused on technical skills aligned with STCW standards, limited attention has been paid to leadership, communication, and environmental education. The research sought to answer how maritime training can be enhanced to address these gaps. Using a systematic literature review and qualitative analysis of insights from maritime professionals, educators, and graduates, the study synthesized theoretical frameworks with real-world experiences. Data were collected through semi-structured interviews and questionnaires, analyzed using thematic coding, and triangulated with findings from the literature review. The results demonstrate strong technical training aligned with STCW standards but reveal fragmented sustainability integration and inadequate leadership preparation. Simulation-based training was identified as highly effective, though it requires support from mentorship and real-world experiences. The findings provide actionable recommendations for enhancing curricula, fostering industry-academic partnerships, and refining policies to better prepare deck officers for modern maritime challenges. This research offers a practical roadmap for transforming maritime education, ensuring safety, operational efficiency, and sustainability in global maritime operations.